(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Nowadays there is no doubt that enterprises should keep changing to im-prove products and services. Flexibility of operation and new solutions in man-agement and first of all innovations will be indispensable to keep competitive position. For enterprising company innovations are obligation. Innovation is an idea, action, thing which is new and has better quality what leads us to competi-tive advantage of enterprise.